Question 3. The true statements are:
4g2 – g = g2(4 – g) ⇒ should be: 4g² - g = g(4g - 1)
9g3 + 12 = 3(3g3 + 4) ⇒ should be: 9g³ + 12 = 3(3g³ + 4) TRUE
24g4 + 18g2 = 6g2(4g2 + 3g) ⇒ should be: 24g⁴ + 18g² = 6g²(4g² + 3)
<span>35g5 – 25g2 = 5g2(7g3 – 5) </span>⇒ should be: 35g⁵ - 25g² = 5g²(7g³ - 5) TRUE
Question 4. Completely factored.
16y⁵ + 12y³ = 4y³(4y² + 3) FACTORED COMPLETELY
18y³ - 6y = 6y(3y² - 1)
20y⁷ + 10y² = 10y²(2y⁵ + 1)
32y¹⁰ - 24 = 8(4y¹⁰ - 3) FACTORED COMPLETELY
<h2>
Answer:</h2><h2>
If she continues to throw darts 75 more times, she could predict to hit the
</h2><h2>
bull's-eye 15 times.</h2>
Step-by-step explanation:
Shay found that she hit the bull's-eye when throwing darts
times =
.
In five times, she will hit the dart once.
If she continues to throw darts 75 more times,
the probability that she will hit the bull's eye =
(75) = 15 times.
If she continues to throw darts 75 more times, she could predict to hit the
bull's-eye 15 times.
Parallel lines have the same slope. for example, the two lines y = 6x + 3 and
y = 6x - 5 are parallel because they have the same slope, 6x.
the slopes of perpendicular lines are opposite reciprocals, which means that you would flip the numbers of the fraction and make it negative. for example, the opposite reciprocal of -3x is 1/3x.
also, parallel lines never intersect, whereas perpendicular lines intersect at a 90 degree angle.
therefore, it isnt possible for two lines to be both parallel and perpendicular.
<h2>Answers :</h2>
a) There are <u>5 subjects</u> in Grade six.
b) 5+7+4+4+5 = There are <u>2</u><u>5</u><u> </u><u>students</u><u> </u> in Grade six.
c) My favourite subject is <u>Maths</u>.
d) My classes start at <u>12 noon.</u>
<h2>So ,</h2>
The question can be :
<h3>What is the class schedule, number of students and subjects in Grade 6? </h3>
Answer:
f(x) = 0.43 *
*
*(x + 10)
Step-by-step explanation:
We have a 6th degree polynomial f(x)
r = 3 is a root of f with multiplicity 2
r = 1 is a root of f with multiplicity 3
f(-5) = -29721.6
f(-10) = 0
Then: f(x) = a*((x -3)^2 ) * ((x - 1)^3)*(x + 10)
f(-5) = a * (-8)^2 * (-6)^3 * (5) = -29,721.6
a* (64) * (-216)* 5 = -29,721.6
-a*69,120 = -29,721.6
a = -29,721.6/-69,120
a = 0.43
so
f(x) = 0.43 *
*
*(x + 10)